The advancement in global halal industry from farm to fork - Harati, Azade; Farzaneh, Parisa (Journal of Halal Product and Research (JHPR), 2024)
In light of the increasing Muslim population worldwide, it is crucial to pay attention to their lifestyle and regulations. This is particularly important for facilitating trade with Muslim nations, especially since the majority of exporters to these nations are non-Muslim. The terms "Halal" and "Haram" hold significant value in the Muslim world, as they refer to what is permissible and forbidden, respectively, according to religious guidelines (Shari’ah). Global trade and the attachment of the Halal logo to products rely on these terms. Interestingly, non-Muslims have shown a positive attitude towards Halal products, believing that they are manufactured in a more hygienic, tasty, and safer manner. However, there are challenges that need to be addressed, such as the lack of an unified Halal certification and regulations for the entire Muslim world, particularly in the era of globalization. There is an urgent need for globally accepted Halal guidelines and regulations that cover the entire supply chain, including processing, logistics, technologies, retail and wholesale, marketing, and branding. This will ensure Halal integrity and enhance trade between non-Muslim and Muslim countries Keywords: Halal, Haram, Globalization, Halal Certification, Halal integration